اتخاذ القرارات التفاعلية لمسألة الأمثَلة المتعددة الأهداف الضبابية (Latakia University Journal -Basic Sciences Series, 2018)
نقدم في هذا البحث طريقة اتخاذ قرارات تفاعلية لمسائل الأمثَلة المتعددة الأهداف مع وجود وسائط ضبابية في توابع الهدف، وتعالج تلك الوسائط كأعداد ضبابية. يحدد متخذ القرار الدرجة  a  للمجموعة  a-مرتبة، وعند كل تكرار يكون على متخذ القرار تخمين الأوزان الوسطية المقايضة، ووفقاً للطريقة المقترحة يتم صياغة مسألة الأمثَلة المتعددة الأهداف الضبابية كمسألة مكافئة غير ضبابية، وتستخدم تلك الطريقة الأوزان الوسطية المقايضة وتولد ما يسمى القاطع المقايض وذلك للحصول على الحل a-بارتو الأمثل (a-Pareto optimal). In this paper, we present an interactive decision making method for multiobjective optimization problems with fuzzy parameters in the objective functions. Theses fuzzy parameters are characterized by fuzzy numbers. The decision maker specifies the degree a of the a-level set. At each iteration, the decision maker is asked to estimate the tradeoff compromise weights. The proposed method involves formulation of fuzzy multiobjective optimization problem as nonfuzzy equivalent problem, and uses the tradeoff compromise weights and generates a so-called tradeoff cut for obtaining the a-Pareto optimal solution.